Workplace crime and inequality: Gender differences in punishments received. Issue 6 (13th August 2018) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: In male-dominated professions such as accounting, gender disparity exists when transgressions are committed. Women are at the risk of receiving harsher sentences than their male counterparts in various situations. Greater representation of women on disciplinary panels and concealing of gender during trials are measures which can help reduce the level of bias that currently prevails. Practical Implications: The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.